2017
DOI: 10.1161/jaha.116.004332
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nonuse of a High‐Potency Statin After an Acute Coronary Syndrome: Insights From the Stabilization of Plaques Using Darapladib‐Thrombolysis in Myocardial Infarction 52 (SOLID‐TIMI 52) Trial

Abstract: BackgroundHigh‐potency statins reduce cardiovascular events after acute coronary syndromes but remain underused in clinical practice. We examined predictors of nonuse of high‐potency statins after acute coronary syndromes.Methods and ResultsThe Stabilization of pLaques usIng Darapladib‐Thrombolysis in Myocardial Infarction (SOLID‐TIMI 52) trial enrolled patients after an acute coronary syndrome in 36 countries between 2009 and 2011. Statin use was strongly encouraged throughout the trial, and statin potency wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Data have shown that, in patients with recent ACS, HIS provided greater protection against death or major cardiovascular events than LMIS [ 7 ], emphasizing the need for adherence to guideline-directed statin use in ACS [ 13 ]. In a recent study, older age, female sex, renal dysfunction, and heart failure during hospital admission were the most common baseline characteristics of non-use of “high-potency statins” [ 25 ]. Factors that have been linked with an increased likelihood of being prescribed a HIS in high CV risk patients include male sex [ 21 ], no previous statin use [ 26 , 27 ], younger age [ 28 ], presence of hypertension [ 28 ], and receiving prescription from a cardiologist [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown that, in patients with recent ACS, HIS provided greater protection against death or major cardiovascular events than LMIS [ 7 ], emphasizing the need for adherence to guideline-directed statin use in ACS [ 13 ]. In a recent study, older age, female sex, renal dysfunction, and heart failure during hospital admission were the most common baseline characteristics of non-use of “high-potency statins” [ 25 ]. Factors that have been linked with an increased likelihood of being prescribed a HIS in high CV risk patients include male sex [ 21 ], no previous statin use [ 26 , 27 ], younger age [ 28 ], presence of hypertension [ 28 ], and receiving prescription from a cardiologist [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen studies did not measure and categorize the non-responders [6], [7], [9], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26]. There were nine studies [10], [18], [24], [27], [28], [29], [30], [31], [32] collecting data on statin use directly from the patients either by interview or selfreporting. By assessing the quality among the selected studies related to question number 13, missing data/ loss to follow-up was higher than 20% in the three studies [28], [33], [34].…”
Section: Study Qualitymentioning
confidence: 99%
“…Referring to question number 18, six studies [8], [15], [21], [35], [36], [37] did not report their study limitation in the discussion part. Thirteen out of 41 studies declared their conflict of interest according to question number 19 in the checklist [9], [10], [16], [18], [19], [24], [26], [28], [33], [34], [38], [39], [40]. Twelve studies did not receive the ethic committee approval nor the participant consent [6], [8], [14], [19], [21], [24], [25], [26], [33], [37], [38], [41].…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“… 1 The 2013 Chinese expert consensus also emphasized that regardless of the baseline cholesterol levels, all patients with ACS events should immediately initiate and maintain intensive statin therapy long-term after discharge. 2 , 3 Based on the results of large-scale clinical trials, early intensive statin therapy has been recommended for patients with recent ACS events. Both epidemiological and interventional clinical trials have shown a strong association between elevated LDL-C level and cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%